A Study of Compaction Densification Behavior of Composite Particles by Multiparticle Finite Element Method. (10th February 2022) - Li, Junnan; Han, Peng; Xu, Yingshi; Liu, Kun; Zhang, Guoxin; Xu, Peng
Abstract : In this paper, 3D particulate scale modelling on the die compaction of DEM generated initial packings of both soft and hard particles was conducted by employing the multiparticle finite element method (MPFEM). The effects of initial packing structures as well as the compaction pressure on the macroscopic and microscopic properties of the whole powder mass and local structures were investigated. In addition, corresponding physical experiments were carried out for model validation. The results show that the compact obtained from the initial dense packing under vibration undergoes yielding stage earlier than that with natural initial packing (without vibration), and the relative density is much higher. Pores that are significantly smaller and with more uniform size and homogenous stress distribution are observed in the former case. Highest stress regions occur in most cases at a grain boundary with large curvature after deformation. Moreover, the high stress in the central part of both soft and hard particles during compaction is significantly reduced after pressure unloading, reaching a new force balance. In this case, the stress is concentrated mainly at the corners of the deformed particles, which creates the risk of cracking during subsequent sintering at either the contact region between particles or the corners. The numerical results are found to be in good agreement with those from physical experiments, confirming the robustness and reliability of the numerical model used in the simulations.